Danaparoid—Consensus Recommendations on Its Clinical Use - Rupert M. Bauersachs; Edelgard Lindhoff-Last; Robert Klamroth; Andreas Koster; Marc Schindewolf; Harry Magnani (Pharmaceuticals)
(1) Background: Danaparoid sodium is a heparinoid antithrombotic that has been used for over 40 years for prophylaxis of DVT in non-HIT patients and for the treatment of heparin-induced thrombocytopenia (HIT) with and without thrombosis. This update summarises current information on its pharmacology and reviews danaparoid dose management in a broad spectrum of clinical situations, including off-label indications. (2) Methods: Evidence from published clinical studies, case reports, compassionate use of danaparoid, and spontaneously reported serious adverse events is summarised and analysed by an interdisciplinary expert group to develop a consensus on dosing regimens of danaparoid for complex clinical situations, including vulnerable patient populations. (3) Results: Dosing regimens are proposed, together with monitoring recommendations and target anti-factor Xa ranges. (4) Conclusion: In a comprehensive summary detailed interdisciplinary dosing recommendations are described to provide a basis for safe and effective use of danaparoid.